2011
DOI: 10.1111/j.1600-0838.2010.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Scapular positioning and movement in unimpaired shoulders, shoulder impingement syndrome, and glenohumeral instability

Abstract: The purpose of this manuscript is to review the knowledge of scapular positioning at rest and scapular movement in different anatomic planes in asymptomatic subjects and patients with shoulder impingement syndrome (SIS) and glenohumeral shoulder instability. We reviewed the literature for all biomechanical and kinematic studies using keywords for impingement syndrome, shoulder instability, and scapular movement published in peer reviewed journal. Based on the predefined inclusion and exclusion criteria, 30 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(113 citation statements)
references
References 35 publications
2
104
1
6
Order By: Relevance
“…Although it was not possible to compare findings of this study with those previously reported in literature, studies on the reliability of measures of the dynamic movements of shoulder with the same system also found reliability results from good to excellent and SEM values similar to those shown here 9,13,14 .…”
Section: Discussionsupporting
confidence: 36%
See 3 more Smart Citations
“…Although it was not possible to compare findings of this study with those previously reported in literature, studies on the reliability of measures of the dynamic movements of shoulder with the same system also found reliability results from good to excellent and SEM values similar to those shown here 9,13,14 .…”
Section: Discussionsupporting
confidence: 36%
“…Regarding the scapular position in relation to the thorax during maintenance of ortostatia, a variety of results can be found in literature 3,4,9 . The present study found that scapula of dominant limb is at approximately 4° of upward rotation, 31° of medial rotation and 10° of anterior tilt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a lack of posterior tilting of the scapula has frequently been associated with the incidence of shoulder impingement symptoms. It is hypothesized that a reduced scapular posterior tilt reduces the subacromial space and thus potentially creates soft tissue impingement (chronic nociception) (Struyf et al 2011a). There is moderate evidence that the upper trapezius shows increased activity among patients suffering from shoulder impingement symptoms, and the lower trapezius Fig.…”
Section: Introductionmentioning
confidence: 99%